Landscape development and settlement history of the Vecht area (722–1122). Issue 4 (4th January 2016) - Buitelaar, A.L.P.; Borger, Guus J.
Abstract: Based on historical evidence a description in broad outline is provided of landscape and settlement development in the Vecht area north of Utrecht for the period 722–1122 AD. Although the fluvial activity of the Vecht channel was reduced from about 2300 BP onwards, the river retained its economic importance as a shipping route in Early Medieval times according to the appearance of mintage and the spread of tollhouses. In the 8th century the Vecht still was seen as a river and as a branch of the Rhine. At that time the Vecht river discharged into a stretch of water that was named Almeer and was characterised as stagnant. The Almeer is regarded as the successor of Lake Flevo, mentioned by classical authors. Since this body of water is indicated as stagnum, it is unlikely that the water level in the southern part of the Almeer was affected by the Vlie tidal inlet in the north at that time. At the end of the 10th century the Almeer already had substantial dimensions. The building of dikes on the southern forelands of the Zuiderzee and the IJ-Lake started at least about 1200 AD. At the beginning of the timeline, settlement was limited to the natural levees of the river Vecht and its distributaries. The reclamation of the vast peatlands on both sides of the river started around the middle of the 11th century. The opening up of new areas for agriculture and settlement was accompanied by a transformation of the social fabric. In association with the pattern of land division historical information is used to indicate some of the changes that occurred in the Vecht area during that period. The drive to further intensify land use resulted in 1122 AD in the decision to build a dike on the northern bank of the Lower Rhine, since the Vecht is a blind arm of the river Rhine.